Tantangan Pendidikan karakter di era digital - Sagala, Kartika; Naibaho, Lamhot; Rantung, Djoys Anneke (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In a digital environment, students are exposed to various stimulations that can influence the formation of their character. The main challenges include how to teach honesty and responsibility amidst the abundant flow of information, as well as guiding the younger generation to develop digital literacy that is balanced with life values. Other challenges include the development of cyberbullying behavior, social media addiction, and lack of supervision in the use of technology. Collaborative efforts are needed between educators, parents and related parties to create a balanced educational environment, where technology can be a tool that supports character development, not an obstacle to it. Therefore, innovative strategies and holistic approaches need to be implemented so that the character of education remains relevant and effective amidst dynamic changes in this digital era. The aim of this research is to solve the challenges of character education in the digital era and solutions to overcome them. The method used in this research is a library study. The results of this research show that with the right strategy, such as integrating character values in the digital curriculum and actively involving parents, character education in the digital era can become a solid foundation for positive personal development in an increasingly connected generation.